2008
DOI: 10.3329/bjpbg.v21i1.17041
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR CHARACTERIZATION OF FIVE SELECTED BRINJAL (Solanum melongena L) GENOTYPES USING SSR MARKERS

Abstract: Five brinjal (Solanum melongena L.) genotypes were selected for characterization using Simple Sequence Repeats (SSR) markers. All the genotypes showed considerable variation in respect of morphological, anatomical and biochemical aspects. For study of relatedness, plant genomic DNA was extracted by CTAB based method using 11 randomly selected primers produced from Calgene Inc. USA. The primers developed 22 bands through PCR amplification out of which 15 from 3 primers and were polymorphic. Genetic similarities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…RAPD (Random Amplified Polymorphic DNA) marker was singly used by Nunome et al (2001); Demir et al (2010), Sharmin et al (2011) and Sifau et al (2014). Other markers that have so far been used singly or in combined forms include but not limited to the following: AFLP (Amplified Fragment Length Polymorphism) (Mace et al, 1999); RAPD and AFLP (Nunome et al, 2001); SSR (Simple Sequence Repeats) (Nunome et al, 2003;Khorsheduzzaman et al, 2008;Stagel et al, 2008;Hurtado et al, 2012); SSR and RAPD (Demir et al, 2010) and ISSR (Inter Simple Sequence Repeats) (Isshiki et al, 2008;Mahmoud & El-Mansy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…RAPD (Random Amplified Polymorphic DNA) marker was singly used by Nunome et al (2001); Demir et al (2010), Sharmin et al (2011) and Sifau et al (2014). Other markers that have so far been used singly or in combined forms include but not limited to the following: AFLP (Amplified Fragment Length Polymorphism) (Mace et al, 1999); RAPD and AFLP (Nunome et al, 2001); SSR (Simple Sequence Repeats) (Nunome et al, 2003;Khorsheduzzaman et al, 2008;Stagel et al, 2008;Hurtado et al, 2012); SSR and RAPD (Demir et al, 2010) and ISSR (Inter Simple Sequence Repeats) (Isshiki et al, 2008;Mahmoud & El-Mansy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the genetic similarity the result supports the previous findings in brinjal such as Ansari and Singh (2015) who recorded six cluster groups using SAHN cluster analysis UPGMA method which revealed that morphological characters viz., shape, size and peel colour of fruits and plant type showed a positive relationship with the DNA based molecular analysis through SSR markers; Demir et al (2010) found that UPGMA dendrograms were used to examine the genetic relatedness of the genotypes. Khorsheduzzaman et al (2008) estimated genetic similarities of SSR profiles based on Jaccard's coefficient value. The dendrogram generated two clusters and they were clearly distinct and separated from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them were discussed below. The 22 amplified DNA products using nine SSR primers with an average amplification for each primer of 2.2 were noticed in six eggplant genotypes showed 70% monomorphic and 30% polymorphic band through using 9 primers in eggplant genotypes [17]. Nineteen SSRs markers for the molecular characterization of 30 eggplant accessions were studied.…”
Section: IVmentioning
confidence: 99%